Innovative Evaluation Techniques for Assessing Students' Achievement in Mathematics and Sciences - Akujieze M.O (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
This study explores innovative evaluation techniques for assessing students' achievement in mathematics and sciences in the context of Onitsha North Local Government Area (LGA), Anambra State, Nigeria. The research objectives include identifying and examining innovative evaluation techniques, exploring the challenges and opportunities associated with their implementation, investigating the perceptions of teachers regarding their use, and assessing the effectiveness of these techniques in capturing students' mathematical understanding, problem-solving skills, and critical thinking abilities. The study employed a survey design, and data were collected using self-structured questionnaires distributed through Google survey. The participants were secondary school teachers in Onitsha North LGA, with a total of 220 instructors responding to the online survey. The data analysis involved various statistical techniques, including frequency counts, percentages, mean, standard deviation, and analysis of variance (ANOVA). The findings revealed that innovative evaluation techniques such as performance-based assessments, open-ended questions, collaborative and group-based assessments, and performance tasks with rubrics were highly regarded by the respondents. However, technology-enhanced assessments faced some challenges and had a lower mean score. The study also identified challenges such as the lack of training and professional development opportunities for teachers, limited availability of resources and technology, resistance from students and teachers to change, time constraints, and challenges in aligning innovative evaluation techniques with existing policies and guidelines. These findings contribute to the existing body of knowledge by providing insights into the applicability, effectiveness, and challenges associated with the use of innovative evaluation techniques in the local context